The Influence of Brand Equity, Trust, Price, PEOU, and PU on Online Based Crowdfunding Investment - Yulianto, Stefanus; Tanamal, Rinabi (Program Studi Teknik Informatika Universitas Pamulang, 2019)
In this modern era, a lot of that affects the behavior of people in everyday life, such as economic, social, cultural, political, and technological progress. People are beginning to rely on technology to live their activities, from transportation, interaction, browsing, learning, business affairs, to invest. This study aims to determine the effect of Brand Equity, Trust, Price, Perceived Ease of Use, and Perceived Usefulness of purchase intention in an online investment application which in this research will use the expansion of TAM. Data collection methods to be used by the authors is quantitative using questionnaires with the target respondents as much as 100 respondents, the data retrieval process using purposive sampling data. The benefit of research is to know whether Brand Equity, Trust, Price, Perceived Ease of Use, and Perceived Usefulness affect Purchase Intention in an online investment application. Data processing using SPSS regression equation results obtained as follows Y = -0.815 + 0,465 X1 + 0,248 X2 - 0,234 X3 + 0,363 X4 + 0,406 X5, Brand Equity becomes the most influential variables. Thus, it can be concluded that the higher brand of online investment application, so will be increasingly higher purchase intention in online investment application.